Management of Islamic Education Curriculum in Madrasahs: Analyzing Alignment with Labor Market Needs - Oki Dermawan; Zohaib Hassan Sain; Defriyanto; Busmayaril (Yayasan Al Hidayah, 2026)
This article examines the management of the Islamic education curriculum in madrasahs and its alignment with the demands of the labor market. It highlights the challenges faced by madrasahs in Indonesia, including resource limitations, insufficient teacher training, and inadequate infrastructure, which hinder the development of curricula that meet workforce needs. While national educational policies like the Merdeka Curriculum provide flexibility, madrasahs must make significant adjustments to enhance the relevance of their offerings. This study recommends the regular updating of teaching materials, the enhancement of teacher skills through professional development, and the creation of partnerships with industries to ensure curricula remain aligned with labor market demands. The paper further advocates for competency-based education, stakeholder collaboration, and the integration of lifelong learning principles to prepare students for an evolving job market. Additionally, the study proposes future research directions, including longitudinal studies tracking the career trajectories of madrasah graduates, implementation studies on curriculum management, and comparative studies across different regions. Ultimately, this research provides actionable recommendations to improve the alignment of Islamic education curricula in madrasahs with labor market needs.